Peran Pengkaji Hadis dalam Menjaga Eksistensi Sunnah - Radhie Munadi (AL-Fikr, 2021)
The problem of Hadith, if parsed, includes many things, from the authenticity of which many orientalists have been challenged, to expanding to transmission (isnad), the history of changing the verbal tradition in codification into hadith texts, to problem understanding and meaning. This problem occupies an important position as well as substantively giving spirit, reevaluation and reinterpretation of various understandings and interpretations of hadith, including differences in the practice of a hadith. So the role of hadith reviewers is needed so that from maintaining the integrity of the hadith to the level of practice, the hadith or sunnah is maintained. So this research tries to provide scientific treasures in an effort to maintain the existence of the sunnah.